Smart Disaster Governance in Reducing Flood Disaster Risk in Pati Regency based on Geospatial Analysis - Arsynindia, Luthfia Diah; Sejati, Anang Wahyu (Department of Urban and Regional Planning, Universitas Diponegoro, 2024)
Hydrometeorological disasters are disasters that often occur in Indonesia and the frequency of these disasters has increased and has an impact on human safety. So, the need for disaster management that can assist in disaster risk reduction. The existence of a smart city concept can help in changing disaster governance to be smart and can help in increasing community resilience to disasters. One of the districts that often experience disasters and has implemented the smart city concept is Pati Regency. Disaster events in Pati Regency in 2016-2020 experienced an increase of approximately 148 incidents. Judging from the increase in disaster events, there is a need for clear disaster management in reducing risk at each stage (pre, during and after the disaster). The application of the smart city concept in Pati Regency is expected to help with this. So far, there has been no previous research related to smart disaster management in Pati Regency. So, this research needs to be done because in disaster risk reduction it is necessary to have intelligent disaster management. The purpose of this study was to determine the parameters of smart disaster management and priority locations in reducing the risk of flood disasters in Pati Regency. This study uses quantitative methods with scoring techniques to obtain intelligent disaster management parameters.